Intermediate syndrome following organophosphate poisoning: A case report in a low resource and poor socio‐economic setting. Issue 10 (8th October 2022) - Lageju, Nimesh; Neupane, Durga; Jaiswal, Lokesh Shekher; Chapagain, Suresh; Uprety, Pratik; Regmi, Swapnil; Bhandari, Silan
Abstract: Intermediate syndrome with respiratory failure is a serious complication that can be fatal as in our case of a 24‐year‐old‐man who developed intermediate syndrome requiring intubation and respiratory support. Furthermore, the patient's socio‐economic situation significantly impacts the illness's progress and prognosis. Abstract : With this case report, we want to stress how a patient's socio‐economic background affects the course and outcome of a particular disease condition.